Pengaruh Technology Acceptance Model dan Literasi Keuangan Terhadap Keputusan Investasi dengan Pengelolaan Keuangan sebagai Variabel Mediasi (Studi Pada Mahasiswa Rantau Pengguna E-Money di Surabaya): Penelitian - Dian Febiyanti; Raden Johnny Hadi Raharjo (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of the Technology Acceptance Model (TAM) and Financial Literacy on Investment Decisions, with Financial Management as a mediating variable among migrant college students using e-money in Surabaya. The research method employed a quantitative approach with PLS-SEM analysis. The sample consisted of 100 respondents selected using a purposive sampling technique. The results indicate that both TAM and Financial Literacy have a positive effect on Financial Management, which in turn significantly affects Investment Decisions. Furthermore, Financial Management was found to mediate the relationship between TAM and Financial Literacy toward Investment Decisions. These findings provide practical implications for universities and fintech developers to enhance students' financial literacy.